The impact of the Covid-19 pandemic on antimicrobial consumption: a descriptive and correlation analysis in a tertiary care hospital in Portugal - Pedro Alexandre Pinto de Oliveira Castro Lopes (2021)
Introduction: The Covid-19 pandemic poses novel challenges in antimicrobial consumption metrics and stewardship strategies. Covid-19 patients became the major cause of hospital admission during the first wave of the pandemic, often leading to antimicrobial prescription on admission or for treatment of superinfections. The aim of this study was to understand how antimicrobial consumption was impacted in the beginning of the pandemic in a tertiary-care hospital, a reference center for Covid-19. Materials and Methods: A retrospective before-after study was done. Descriptive statistics of discharges, patient-days, and antimicrobial use indicators (DDD/100 discharges, DDD/100 patient-days) for various groups were calculated for the first three months of the pandemic (March, April and May 2020) as a quarterly value, and for each year in 2011-2019, and their annual percentual changes were used to estimate 95% confidence intervals. Indicators were compared to patient typology (medical/surgical), type of admission (urgent/elective) and age groups, using Spearman's correlation coefficient. Results: Statistically significant increases occurred in 2020 for total antimicrobials, antibiotics, antifungals, antivirals, macrolides, cephalosporins, amoxicillin + clavulanic acid, carbapenems, and 3rd generation cephalosporins, while a reduction was seen in cefazolin + cefoxitin. In 2020, there was a different impact in DDD/100 discharges and DDD/100 patient-days, due to increased lengths-of-stay and longer antimicrobial therapy. Conclusion: The Covid-19 pandemic led to an increase in antimicrobial consumption with a different impact in each indicator studied. This highlights the need to use both indicators simultaneously to better understand the causes of antimicrobial consumption variation and improve the design of effective antimicrobial stewardship interventions.